An Integrated Model of Ethical Decision-making: a Proposed Pedagogical Framework for a Marketing Ethics Curriculum - Agarwal, James (Teaching business ethics, 2002)
This paper presents an integrated model ofethical decision-making in marketing thatincorporates teleological, deontological andexistential theory. First, this frameworkprovides a descriptive model, which enables thedecision-maker to evaluate each step of thedecision-making process from three disparateperspectives in order to ensure a morecomprehensive ethical decision – that is, onewhich is good, right, and authentic. A set ofmoderating factors that influence the processand the outcome of the ethical decision-makingprocess is also identified. Second, we proposea pedagogical framework in developing a set ofmodules for a course curriculum on ethicaldecision-making in marketing. It has beenargued that the approaches to teachingmarketing ethics have traditionally been basedupon normative theories and that students ofmarketing ethics have been deprived of theopportunity to personalize their value systemsin ethical situations. Our proposed integratedframework allows for the student to applypersonal values to bear on the decision contextsince existentialism, at the core foundation,is really a theory of choice.